2016
DOI: 10.1021/acs.orglett.6b00304
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Direct Thiolation at α-C(sp3)–H of Ethers with Disulfides Using Acridine Red as Photocatalyst

Abstract: A simple and efficient method for the preparation of α-arylthioethers through a visible-light-induced direct thiolation at α-C(sp(3))-H of ethers with diaryl disulfides was developed using acridine red as a novel photocatalyst. The reactions occurred at ambient conditions and generated the corresponding products in good to excellent yields, ignoring steric effect of disulfides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 54 publications
2
46
0
1
Order By: Relevance
“…Li and Wang developed a method for the α-C(sp 3 )–H thiolation of ethers, using Acridine Red as photosensitizer and tert -butyl hydroperoxide (TBHP) as oxidant ( Scheme 38 ) [ 73 ]. They reported that photoexcited Acridine Red performs an energy transfer on TBHP, which homolytically decomposes to generate a hydroxyl radical and a tert -butoxyl radical.…”
Section: Reviewmentioning
confidence: 99%
“…Li and Wang developed a method for the α-C(sp 3 )–H thiolation of ethers, using Acridine Red as photosensitizer and tert -butyl hydroperoxide (TBHP) as oxidant ( Scheme 38 ) [ 73 ]. They reported that photoexcited Acridine Red performs an energy transfer on TBHP, which homolytically decomposes to generate a hydroxyl radical and a tert -butoxyl radical.…”
Section: Reviewmentioning
confidence: 99%
“…Disulfides, as versatile synthetic precursors, have been applied to a variety of photochemical reactions, [10] but only a few studies have been reported about photodriven difunctionalization without a photocatalyst, particularly when introducing different groups into carbon-carbon double bonds in one step, has not yet been addressed. [11] In our recent studies on phototriggered transformation with photocatalyst-free conditions, [12] we attempted to further examine the possibility of a reaction between disulfides and styrenes; however, we did not observe a reaction under nitrogen (N 2 ) with blue light-emitting diode (LED) irradiation.…”
Section: Hydroxysulfurization; Alkoxysulfurizationmentioning
confidence: 99%
“…Acridine red was used as a photocatalyst for the visible light-induced direct thiolation of ethers (Figure 17) [52]. The thiolation of tetrahydrofuran (THF) using diphenyl disulfide 47 was carried out in the presence of acridine red (2 mol%) and tert-butyl hydroperoxide (TBHP) as an oxidant.…”
Section: Visible-light Photocatalysis Of Carbon-based Materialsmentioning
confidence: 99%